A reflexive methodology for de-westernizing the subfield of Latin American Organizational Communication (Intercom - Brazilian Journal of Communication Sciences, 2022)
This paper aims to develop a reflexive methodology to explore the production of knowledge of the subfield of Organizational Communication research, considering the contextual, institutional, and cultural realities of the Latin American region. For this purpose, responding to the recent calls to de-westernized Communication, this paper adopted a “bottom-up” approach, which favors the realities experienced by Latin American Organizational Communication researchers and scholars. The proposed methodology provides a model that can serve as an example to de-westernize knowledge production in related fields.
Keywords: Latin America; De-Westernizing; Methodology